Native mass spectrometry provides sufficient ion flux for XFEL single-particle imaging - Uetrecht, Charlotte (International Union of Crystallography, 2019)

(untitled) (J Synchrotron Radiat)
The SPB/SFX instrument at the European XFEL provides unique conditions for single-particle imaging (SPI) experiments due to its high brilliance, nano-focus and unique pulse structure. Promising initial results provided by the international LCLS (Linac Coherent Light Source) SPI initiative highlight the potential of SPI. Current available injection methods generally have high sample consumption and do not provide any options for pulsing, selection or orientation of particles, which poses a problem for data evaluation. Aerosol-injector-based sample delivery is the current method of choice for SPI experiments, although, to a lesser extent, electrospray and electrospinning are used. Single particles scatter only a limited number of photons providing a single orientation for data evaluation, hence large datasets are required from particles in multiple orientations in order to reconstruct a structure. Here, a feasibility study demonstrates that nano-electrospray ionization, usually employed in biomolecular mass spectrometry, provides enough ion flux for SPI experiments. A novel instrument setup at the SPB/SFX instrument is proposed, which has the benefit of extremely low background while delivering mass over charge and conformation-selected ions for SPI.